2021
DOI: 10.1155/2021/9961189
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA HCG11 Acts as a Tumor Suppressor in Gastric Cancer by Regulating miR-942-5p/BRMS1 Axis

Abstract: The functions of long noncoding RNAs (lncRNAs) have been widely investigated in human cancers, including gastric cancer (GC). The purpose of this study was to elucidate the role of lncRNA HCG11 in GC. In this study, mRNA and protein expressions were detected by quantitative real-time polymerase chain reaction assays (RT-qPCR) and Western blot analysis. The proliferation ability of GC cells was examined by (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyl Tetrazolium Bromide) MTT assays. The invasion and migration abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…More importantly, we verified that miR-942-5p is involved in regulating the proliferation and apoptosis of PMECs. Many studies have shown that miR-942-5p regulates cell proliferation and disease progression in different types of tumors ( Li et al, 2020 ; Wang et al, 2020 ; Gu et al, 2021 ; Zhang et al, 2021 ); these findings are consistent with our results, because PMECs dysfunction in PH is a cancer cell-like phenotype. However, Wang et al found that miR-942-5p could inhibit PASMCs proliferation in vitro ( Wang et al, 2021 ), which is inconsistent with our results; a possible reason for this is the difference in the cell types studied and the cell culture conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More importantly, we verified that miR-942-5p is involved in regulating the proliferation and apoptosis of PMECs. Many studies have shown that miR-942-5p regulates cell proliferation and disease progression in different types of tumors ( Li et al, 2020 ; Wang et al, 2020 ; Gu et al, 2021 ; Zhang et al, 2021 ); these findings are consistent with our results, because PMECs dysfunction in PH is a cancer cell-like phenotype. However, Wang et al found that miR-942-5p could inhibit PASMCs proliferation in vitro ( Wang et al, 2021 ), which is inconsistent with our results; a possible reason for this is the difference in the cell types studied and the cell culture conditions.…”
Section: Discussionsupporting
confidence: 93%
“…In those miRNAs, qRT-PCR showed that miR-942-5p was upregulated in hypoxia-induced PMECs, and diminished after overexpression of circGSAP levels ( Figures 3A,B ), which is consistent with the miRNA acts as circRNA sponge to influence the occurrence and development of diseases. and miR-942-5p regulates cell proliferation had been reported ( Li et al, 2020 ; Wang et al, 2020 ; Gu et al, 2021 ; Zhang et al, 2021 ), so, we speculate that miR-942-5p may be downstream of circGSAP, which affecting the function of PMECs. Then, potential binding sites between circGSAP and miR-942-5p were predicted using Circular RNA Interactome, and the representative putative target sites of miR-942-5p are shown in Figure 3C .…”
Section: Resultsmentioning
confidence: 61%
“…By altering miR-144-3p/PBX3 axis, lncRNA HCG11 knockdown slows the growth of ovarian cancer cells (41). lncRNA HCG11 controls the miR-942-5p/BRMS1 axis to act as a tumor suppressor in GC (42). By increasing SOCS5, the long non-coding RNA HCG11 sponging miR-522-3p prevents the growth of non-small cell lung cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to fathom out the functional role of HCG11 in the regulation of CRC cell malignant behaviors. Based on previous literature, HCG11 was verified as a tumor suppressor in several malignancies, including gastric cancer [ 31 ] and cervical cancer [ 32 ] while HCG11 was also suggested as an oncogenic factor in ovarian cancer [ 33 ]. In the current study, HCG11 was detected to be aberrantly overexpressed in CRC cell lines, and based on results of functional assays, we confirmed that HCG11 silence could promote the apoptosis of CRC cells while inhibiting cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…MALAT1 was corroborated as a ceRNA to exert oncogenic influences on CRC [ 37 ]. Additionally, HCG11 was verified to sponge miR-942-5p to enhance BRMS1 expression, thus affecting the biological behaviors of gastric cancer cells [ 31 ]. Consistent with recent studies, HCG11 was validated as a molecular sponge of miR-26b-5p, targeting ARPP19 to positively modulate ARPP19 expression.…”
Section: Discussionmentioning
confidence: 99%